2017
DOI: 10.1186/s12887-016-0755-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined music and touch intervention on pain response and β-endorphin and cortisol concentrations in late preterm infants

Abstract: BackgroundPreterm neonates undergo many painful procedures as part of their standard care in the neonatal intensive care unit. However, pain treatment is inadequate in many of these routine procedures. In the present study, we investigated the impact and mechanism of combined music and touch intervention (CMT) on the pain response in premature infants.MethodsSixty-two preterm neonates (gestational age of <37 weeks) were randomly assigned to either the experimental or control group. Infants in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 44 publications
4
61
0
5
Order By: Relevance
“…In fact, many of our most rigorous studies also had dependent measures that did not demonstrate impacts under musical intervention. Qiu et al . did not find any change in salivary cortisol, Butt and Kisilevsky found no improvement in arterial oxygen saturation level, and Keith et al .…”
Section: Selection Of Studies and Overview Of Findingsmentioning
confidence: 94%
See 4 more Smart Citations
“…In fact, many of our most rigorous studies also had dependent measures that did not demonstrate impacts under musical intervention. Qiu et al . did not find any change in salivary cortisol, Butt and Kisilevsky found no improvement in arterial oxygen saturation level, and Keith et al .…”
Section: Selection Of Studies and Overview Of Findingsmentioning
confidence: 94%
“…In fact, many of our most rigorous studies also had dependent measures that did not demonstrate impacts under musical intervention. Qiu et al 10 did not find any change in salivary cortisol, Butt and Kisilevsky 68 found no improvement in arterial oxygen saturation level, and Keith et al 65 found no change in arterial pressure. So, although the high rate of positive findings in the literature points towards music's potential to moderate the stress response, these null findings reiterate the need for continued research in this area with greater attention to systematic replication, proper control conditions, and blinding of experimental and hospital staff.…”
Section: Selection Of Studies and Overview Of Findingsmentioning
confidence: 95%
See 3 more Smart Citations